ANALISIS PROSES PEMBELAJARAN BIOLOGI KELAS X MADRASAH ALIYAH NEGERI SUMPUR - Zikra, Zikra; Lufri, Lufri; Razak, Abdul (Kolaboratif, 2013)
The low value of the students in the subjects of biology at Madrasah Aliyah Sumpur seen some of the factors that affect the learning outcomes one of which is the learning process. The learning process is one of the critical success factors in learning. To obtain a good learning must be supported by a good learning process and effective. In addition, the learning often occurs in terms of issues such as teachers, students, facilities, and infrastructure. This research is a descriptive study with a qualitative approach. Data validity checking technique used is the technique of triangulation. The data were analyzed qualitatively. Based on the results of analysis of the learning process can be concluded as follows (1) Planning Learning in terms of the format is in accordance with aspects of assessment in the IPKG-1. Based on the study of documentation in terms of content, learning Implementation Plan (RPP) is not in accordance with the syllabus (2) The general teaching is in conformity with the appraisal aspect IPKG-2 (3) assessment / evaluation of learning is done in the capture of the cognitive aspects of the value daily tests. Affective and psychomotor assessments taken from the attitude and skills of the student assessment for learning (4) learning problems that occur specifically in learning biological medium category (2.23). The problem there in terms of teachers, students, facilities and infrastructure.